Chikungunya virus vaccine: a decade of progress solving epidemiological dilemma, emerging concepts, and immunological interventions - Shaikh, Mohd Sayeed; Faiyazuddin, Md.; Khan, Mubasshera Sabir; Pathan, Shahbaz K.; Syed, Imran J.; Gholap, Amol D.; Akhtar, Mohammad Shabib; Sah, Ranjit; Mehta, Rachana; Sah, Sanjit; Bonilla-Aldana, D. Katterine; Luna, Camila; et al. (Frontiers in Microbiology, 2024)
Chikungunya virus (CHIKV), a single-stranded RNA virus transmitted by Aedes mosquitoes, poses a significant global health threat, with severe complications observed in vulnerable populations. The only licensed vaccine, IXCHIQ, approved by the US FDA, is insufficient to address the growing disease burden, particularly in endemic regions lacking herd immunity.Monoclonal antibodies (mAbs), explicitly targeting structural proteins E1/E2, demonstrate promise in passive transfer studies, with mouse and human-derived mAbs showing protective efficacy. This article explores various vaccine candidates, including live attenuated, killed, nucleic acid-based (DNA/RNA), virus-like particle, chimeric, subunit, and adenovirus vectored vaccines. RNA vaccines have emerged as promising candidates due to their rapid response capabilities and enhanced safety profile. This review underscores the importance of the E1 and E2 proteins as immunogens, emphasizing their antigenic potential. Several vaccine candidates, such as CHIKV/IRES, measles vector (MV-CHIK), synthetic DNA-encoded antibodies, and mRNA-lipid nanoparticle vaccines, demonstrate encouraging preclinical and clinical results. In addition to identifying potential molecular targets for antiviral therapy, the study looks into the roles played by Toll-like receptors, RIG-I, and NOD-like receptors in the immune response to CHIKV. It also offers insights into novel tactics and promising vaccine candidates. This article discusses potential antiviral targets, the significance of E1 and E2 proteins, monoclonal antibodies, and RNA vaccines as prospective Chikungunya virus vaccine candidates.